Aflatoxin biocontrol in practice requires a multidisciplinary, long-term approach - Ortega-Beltran, A.; Bandyopadhyay, R. (Frontiers Media, 2023)
One of the most elusive food safety problems is the contamination of staple crops with the highly carcinogenic aflatoxins produced by Aspergillus section Flavi fungi. Governments, farmers, institutions, consumers, and companies demand aflatoxin solutions. Many aflatoxin management technologies exist, but their real-life use and effectiveness is determined by diverse factors. Biocontrol products based on atoxigenic isolates of A. flavus can effectively reduce aflatoxins from field to fork. However, development, testing, and registration of this technology is a laborious process. Further, several barriers prevent the sustainable use of biocontrol products. There are challenges to have the products accepted, to make them available at scale and develop mechanisms for farmers to buy them, to have the products correctly used, to demonstrate their value, and to link farmers to buyers of aflatoxin-safe crops. Developing an effective aflatoxin management technology is the first, major step. The second one, perhaps more complicated and unfortunately seldomly discussed, is to develop mechanisms to have it used at scale, sustainably, and converged with other complementary technologies. Here, challenges and actions to scale the aflatoxin biocontrol technology in several countries in sub-Saharan Africa are described with a view to facilitating aflatoxin management efforts in Africa and beyond.